La psicomotricidad y lectoescritura en niños de cinco años Institución Educativa Inicial N° 397 Corazón de Jesús Belén 2024 - Yalta Navarro, Sonia Patricia (2025)
The study's general objective was to determine the relationship between psychomotor skills and literacy in five-year-old children at the Corazón de Jesús Belén 2024 Initial Educational Institution. The research was descriptive-quantitative; a correlational cross-sectional design was used; the sample consisted of 98 children and a sample of 69. Two observation guides were used as instruments. The study found that children were at the Intermediate level in psychomotor skills, with 72.5%, and at the High level in literacy, with 46.4%. In conclusion, there is statistical evidence to affirm a low, positive relationship between the psychomotor and literacy variables.